(67-5×9+63:7-30)×(6×6)
Răspunsuri la întrebare
Răspuns de
0
(67-45+9-30 ) x36=
1x36=36
1x36=36
Răspuns de
1
(67-5x9+63:7-30)x(6x6)
(67-45+9-30)x36
(22+9-30) x 36
(31-30) x36
1x 36 =36
sper ca te-am ajutat
(67-45+9-30)x36
(22+9-30) x 36
(31-30) x36
1x 36 =36
sper ca te-am ajutat
Alte întrebări interesante
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă